Improving polylactide toughness by plasticizing with low molecular weight polylactide-poly(Butylene succinate) copolymer - Srithep, Yottha; Veang-In, Onpreeya; Pholharn, Dutchanee; Turng, Lih Sheng; Morris, John (My University, 2021)
A low-molecular-weight polylactide-poly(butylene succinate) (PLA-PBS) copolymer was synthesized and incor-porated into polylactide (PLA) as a novel toughening agent by solvent casting. The copolymer had the same chemical structure and function as PLA and it was used as a plasticizer to PLA. The copolymer was blended with PLA at a weight ratio from 2 to 10 wt%. Phase separation between PLA and PLA-PBS was not observed from their scanning electron microscopy (SEM) images and the crystal structure of PLA almost remained unchanged based on the X-ray diffraction (XRD) measurement. The melt flow index (MFI) of the blends was higher as the amount of PLA-PBS increased, indicating that the block copolymer did improve the mobility of the PLA chains. Moreover, tensile tests revealed that PLA with greater PLA-PBS copolymer exhibited higher elongation at break and it reached the maximum at 8 wt% of PLA-PBS in PLA, which was around 6 times higher than that of pure PLA. Furthermore, the glass transition temperature, measured by differential scanning calorimetry (DSC), mark-edly decreased with an increasing amount of the copolymer as it decreased from 61.2°C for pure PLA to 41.3°C when it was blended with 10 wt% PLA-PBS copolymer. Therefore, the PLA-PBS copolymer was shown to be a promising plasticizer for fully biobased and toughened PLA.
Keywords: Biodegradability; Low molecular weight copolymer; Plasticizer; Poly (butylene succinate); Polylactide